Large scale studies with concept mapping - Priit Reiska; Katrin Soika (Universidad de Granada, 2013)
Concept mapping is a method for determining the achievement of knowledge. Concepts are linked with labelled lines to proposition and so the concepts create a graphical structured meaningful relationship. There are many ways to use concept mapping in research as data collecting and assessment instrument. Changing the conditions (like focus question about the concept map, lists of concepts, given structure of concept map etc.) also change the results. For a valid research is necessary to analyse the study and define the aims before collecting the data. Probably the most comfortable concept mapping constructing opportunity is to use special Internet based environment and analysing program - that makes data collection easier and more objective. This article brings out, what kind of problems may occur, when concept mapping method is used as a research instrument in a large scale study and it also tries to define how to select the a valid instrument for a study. Researchers want to analyse studentsʼ knowledge, but instead sometimes they can only control whether they were able to create concept maps. The study brought out, that the quality of concept maps does not depend on concept maps creating frequency and computer handling skills.